Dissolution testing of herbal medicines: challenges and regulatory standards in Europe, the United States, Canada, and Asia - Disch, Lucia; Drewe, Juergen; Fricker, Gert (Dissolution technologies, 2017)
Herbal medicines are the oldest method for treating diseases and at the same time still the most commonly used worldwide. Although people in developing countries depend on traditional herbal medicines, herbal products also play an important role in the healthcare systems of industrialized countries due to ongoing health trends for substituting natural products for potentially harmful chemicals. The regulatory standards of various authorities for herbal medicines are not harmonized in regional classification and quality requirements. It is particularly difficult to oversee authority requirements for dissolution testing of herbal medicines due to widely varying regulations. The aim of this article is to give a short overview of regulatory classification and dissolution standards of herbal medicinal products with regard to regional differences in Europe, the United States, and Asia. Furthermore, challenges in dissolution method development for herbal medicines are discussed. Because the ingredients of herbal medicinal products often cover a mixture of multiple herbal constituents, dissolution method development is much more complex than for defined single constituents.
Gesehen am 17.04.2018